MANAGEMENT OF URETER STONES USING ESWL COMPARED TO URS - Muhammad Omar Rusydi; Djoko Rahardjo (Jurnal Urologi Indonesia, 2013)
Objective: To evaluate the management of ureterolithiasis using Extracorporeal Shock Wave Lithotripsy (ESWL) EDAP Sonolith Technomed compared to ureteroscopy (URS) with holmium:YAG laser lithotripsy. Material & Method: Research was conducted at Central Pertamina Hospital Jakarta by comparative analysis. The data was taken from patients’ medical records diagnosed with ureterolithiasis who had been treated from January to Desember 2009.Results: Central Hospital Pertamina Jakarta had treated 127 patients with urolithiasis from January to December 2009. Most frequent therapeutic modality was URS, which was followed by ESWL.Double J stents were used in 19,8% of the treatmentin combination with URS, more common than ESWL. Stone free rate in urolithiasis was not significantly different between treatment with URS and ESWL, although stone free rate of URS was higher than ESWL.Use of DJ stent didn’t affect stone free rate of urolithiasis from two of these modalities.Conclusion: Stone free rate of these modalities was below of stone free rate at literatures published, because evaluation from stone free rate of this research was taken after the treatment or 1-2 days after the treatment with imaging of KUB and USG. Keywords: Urolithiasis, extracorporeal shock wave lithotripsy, ureteroscopic,DJ stent, stone free rate.